“I wanted to participate in my own care”: Evaluation of a Patient Navigation Program - Samuels, Elizabeth A. (West J Emerg Med, 2021)
INTRODUCTION: Patient navigation programs can help people overcome barriers to outpatient care. Patient experiences with these programs are not well understood. The goal of this study was to understand patient experiences and satisfaction with an emergency department (ED)-initiated patient navigation (ED-PN) intervention for US Medicaid-enrolled frequent ED users. METHODS: We conducted a mixed-methods evaluation of patient experiences and satisfaction with an ED-PN program for patients who visited the ED more than four times in the prior year. Participants were Medicaid-enrolled, English- or Spanish-speaking, New Haven-CT residents over the age of 18. Pre-post ED-PN intervention surveys and post-ED-PN individual interviews were conducted. We analyzed baseline and follow-up survey responses as proportions of total responses. Interviews were coded by multiple readers, and interview themes were identified by consensus. RESULTS: A total of 49 participants received ED-PN. Of those, 80% (39/49) completed the post-intervention survey. After receiving ED-PN, participants reported high satisfaction, fewer barriers to medical care, and increased confidence in their ability to coordinate and manage their medical care. Interviews were conducted until thematic saturation was reached. Four main themes emerged from 11 interviews: 1) PNs were perceived as effective navigators and advocates; 2) health-related social needs were frequent drivers of and barriers to healthcare; 3) primary care utilization depended on clinic accessibility and quality of relationships with providers and staff; and 4) the ED was viewed as providing convenient, comprehensive care for urgent needs. CONCLUSIONS: Medicaid-enrolled frequent ED users receiving ED-PN had high satisfaction and reported improved ability to manage their health conditions.